Short-term changes in the health state of children with group B meningococcal disease: A prospective, national cohort study. - Iain T R Kennedy; Albert J van Hoek; Sonia Ribeiro; Hannah Christensen; W John Edmunds; Mary E Ramsay; Shamez N Ladhani (PLoS ONE)
Objectives The short-term impact of childhood invasive meningococcal disease (IMD) on quality-of-life (QoL) remains largely unquantified. This study aimed to quantify QoL loss at the point when illness was at its worst, and assess health state recovery in the months following illness. Methods Parents of children aged <16 years with laboratory-confirmed meningococcal group B (MenB) disease in England, with onset dates from November 2012 to May 2013 were asked to complete a short questionnaire, which included EQ-5DY, a version of EQ-5D for 8-15 year-olds. The parents, or child if able, were asked to complete the questionnaires while considering the child's health on the worst day of illness and on the date the questionnaires were completed. Results The overall response rate was 43% (109/254 children), with no significant differences between respondents and non-respondents. The median time from disease onset to questionnaire completion was 134 days (interquartile range (IQR), 92 to 156 days). After imputation, the median health index was -0.056 (IQR, -0.073 to 0.102) on the worst day of illness, and 1 (IQR 0.866 to 1.000) on the date of questionnaire completion. The respective Visual Analogue Scores (VAS) were 6.5/100.0 (IQR, 0.0 to 20.0) and 95.0/100.0 (IQR, 90.0 to 100.0). The health state of cases with long-term sequelae (n = 41) was significantly worse at follow-up than those who recovered uneventfully (n = 64; 90.0 vs. 98.0; p<0.001), although there was no significant difference on the worst day of illness (5.0 vs. 10.0; p = 0.671). Conclusions This work has provided, for the first time, a quantitative estimate of QoL loss at the peak of illness and in the months after MenB disease in children. The magnitude of QoL loss is staggering, with the reported health state being at, or close to, the worst possible outcome imaginable. This study highlights the difficulties in measuring the impact of illness in young children, who often have the highest burden of potentially preventable infectious diseases.